Strengthening evidence-based practice culture in nursing: An ethnographic study in the central highlands of Vietnam - Dang Vuong Nguyen; Apinya Jumpamool (Belitung Nursing Journal, 2026)
Background: Evidence-based practice (EBP) is a vital approach to achieve Quality Improvement (QI) in healthcare services by ensuring that nursing care is grounded in the best available evidence. However, the integration of EBP into nursing in Vietnam is often lacking, presenting a significant challenge for both healthcare leaders and individual practitioners. Objectives: This qualitative study aimed to understand the workplace culture regarding EBP implementation among Vietnamese nurses, exploring the shared beliefs, values, and contextual factors that influence EBP within a tertiary hospital setting, with a particular focus on the Intensive Care Unit and other relevant departments. Method: A focused ethnographic approach was employed. Data were collected over 14 months (from late May 2024 to early July 2025) through participant observation and in-depth interviews with 30 registered nurses from various units (Nursing Department, Intensive Care Unit, Emergency Room, Neurological Department, Internal Medicine Department, and Geriatrics Department). Data analysis followed ethnographic analytic principles to identify key themes. Results: The findings revealed a complex interplay of individual, organizational, and systemic factors. Five key themes emerged: 1) Informal and experiential learning with limited research involvement; 2) Culture of task- and procedure-centered nursing practice; 3) Compliance culture; 4) Developing professional identity; and 5) Misconceptions of EBP and low-evidence conceptualization. Nurses favored experiential and peer-based learning over systematic scientific evidence. Structural constraints, including insurance policies and rigid hierarchies, further hindered EBP implementation. Conclusion: The study recommends multi-level strategies that involve policy reform, hospital management support, and enhanced nursing education to foster an environment conducive to EBP, thereby improving nursing autonomy and the quality of patient care.